The influence of mathematics self-efficacy and mathematics anxiety on students' intrinsic motivation in learning mathematics-related subjects: a multiple linear regression analysis / Nurul Hafizah Azizan ...[et al.] - Azizan, Nurul Hafizah; Hamzah, Nor Hazreeni; Mohamed Zukri, Shamsunarnie; Ibrahim, Nurul Bariyah; Ibrahim, Nur Safwati; Mohd Fauzi, Noor Zafarina; Abdullah, Norshaieda (Universiti Teknologi MARA, Kelantan, 2023)
This study primarily focuses on students' intrinsic motivation. Specifically, the ultimate aim of this study is to investigate the influential factors contributing to students' intrinsic motivation to learn mathematics related subjects. Participants of this study were 137 students ( 45 male and 92 female) from Universiti Teknologi MARA (UiTM) Kelantan Branch, Kota Bharu campus. Data were collected using an online questionnaire which was distributed through the WhatsApp platform. A multiple linear regression analysis was employed to achieve the objective of the study. Results show that both mathematics self-efficacy and mathematics anxiety significantly affect students' intrinsic motivation in learning mathematics related subjects. The study also found that mathematics self-efficacy is the most important factor that contributes to the students' intrinsic motivation.